| | |

| \((f\ +\ g)(x) = f(x)\ +\ g(x)\) | If f(x) = x and g(x) = x – 3, find f(x) + g(x).
\(x\ +\ (x\ −\ 3)\)
\(2x\ −\ 3\) |

| \((f\ −\ g)(x) = f(x)\ −\ g(x)\) | If f(x) = x2 and g(x) = x + 2, find f(x) − g(x).
\(x^{2}\ −\ (x\ +\ 2)\)
\(x^{2}\ −\ x\ −\ 2\) |

| | If f(x) = x + 3 and g(x) = x − 2, find f(x)g(x).
\((x\ +\ 3)(x\ −\ 2)\)
\((x^{2}\ −\ 2x\ +\ 3x\ −\ 6\)
\((x^{2}\ +\ x\ −\ 6\) |

| \((\frac{f}{g})(x) = \frac{f(x)}{g(x)}\)
\((note\ that\ g(x)\ \neq\ 0)\) | If f(x) = x2 + 3x and g(x) = x, find f(x)/g(x).
\(\frac{x^{2}\ +\ 3x}{x}\)
\(\frac{x(x\ +\ 3)}{x}\)
\(x\ +\ 3\) |

| \((f\ \circ\ g)(x) = f(g(x))\) | If f(x) = x2 and g(x) = x + 5, find (f ∘ g)(x).
\(f(g(x)) = f(x\ +\ 5)^{2}\)
\(= x^{2}\ +\ 10x\ +\ 25\) |